2016
DOI: 10.1177/1359105314567211
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, internalized hepatitis (Hepatitis C virus) stigma, and self-esteem: Does spirituality curtail the relationship in the workplace

Abstract: The objective of this study was to examine the impact of workplace bullying on self-esteem, including the mediating effect of internalized stigma and the moderating effect of spirituality, among hepatitis C virus patients. Data were collected from 228 employed hepatitis C virus patients who had been admitted to Gastroenterology and Hepatology wards in Pakistani hospitals. We found support for the hypothesis that workplace bullying is associated with low self-esteem via internalized stigma. In addition, spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Recent work suggests that disease related stigma is less studied in Asian countries (Brohan, Slade, Clement, & Thornicroft, 2010). A few studies have been conducted on disease based stigma like AIDS and HCV in Pakistani context at workplace domain (Bashir, Nasir, Qayyum, & Bashir, 2012;Noor, Bashir, & Earnshaw, 2016). The present study investigates disclosure Tuberculosis stigmatized identities and its workplace outcomes (deviant workplace behavior) through interlinking mechanism of self-esteem that are less studied in previous psycho-social literature.…”
Section: Purpose Of the Studymentioning
confidence: 94%
“…Recent work suggests that disease related stigma is less studied in Asian countries (Brohan, Slade, Clement, & Thornicroft, 2010). A few studies have been conducted on disease based stigma like AIDS and HCV in Pakistani context at workplace domain (Bashir, Nasir, Qayyum, & Bashir, 2012;Noor, Bashir, & Earnshaw, 2016). The present study investigates disclosure Tuberculosis stigmatized identities and its workplace outcomes (deviant workplace behavior) through interlinking mechanism of self-esteem that are less studied in previous psycho-social literature.…”
Section: Purpose Of the Studymentioning
confidence: 94%
“…These findings are similar to internalized stigma studies in other patient populations. 53 , 70 , 114 …”
Section: Internalized or Self-stigma And Stigma Resistancementioning
confidence: 99%
“…Chronic illness stigmatization, most notably characterized in mental health 43 45 and HIV/AIDS 46 48 research, is a common and global social issue. 49 While the majority of research in this area is in the aforementioned conditions, other chronic illnesses such as cancers, 50 52 hepatitis C, 53 55 epilepsy, 56 58 leprosy, 59 61 and obesity 62 65 have well-documented stigmatization. Illness stigma has a myriad of public health implications including limiting access to medical care, increasing treatment nonadherence, increased psychological distress, decreased self-esteem and self-efficacy, and increased illness symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Because chronic diseases often result in social devaluation or stigma [7], they negatively affect the physical and psychosocial health of patients [8]. A previous study found that patients with chronic hepatitis C experience shame, decreased self-esteem, fear, depression, and isolation [9].…”
Section: Introductionmentioning
confidence: 99%